Proceedings of the 7th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design : Dr 2013
DOI: 10.17077/drivingassessment.1511
|View full text |Cite
|
Sign up to set email alerts
|

A Research Synthesis of Text Messaging and Driving Performance

Abstract: Summary:To determine the effects of text messaging on driving performance, all available experimental studies that measured driving performance were identified through a variety of database searches and backtracking strategies, and analyzed using standard research synthesis methods. Fourteen studies with a total of 519 participants were coded and analyzed. Methodology, independent and dependent variables, and statistical analyses varied widely across studies, but conclusions were clear and convergent. Reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Texting while driving is a growing public safety hazard (Caird et al, 2013;Wilson and Stimpson, 2010). For example, a multivariate regression analysis based on the Fatality Accident Reporting System (FARS) database found that the percentage of distractionrelated fatalities increased from 10.9% in 1999 to 15.8% in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Texting while driving is a growing public safety hazard (Caird et al, 2013;Wilson and Stimpson, 2010). For example, a multivariate regression analysis based on the Fatality Accident Reporting System (FARS) database found that the percentage of distractionrelated fatalities increased from 10.9% in 1999 to 15.8% in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing prevalence of smartphones and wearable devices, texting while driving is becoming an important public safety hazard [1]. The National Highway and Traffic Safety Administration (NHTSA) reported that 11% of drivers are using cell phones at any one time [2].…”
Section: Introductionmentioning
confidence: 99%
“…Text-to-speech and voice-recognition technologies may potentially reduce the amount of visual distraction compared to looking down at a phone to read messages [21]. A meta-analysis study found that lateral vehicle control and glances away from the road were less affected by reading text messages than writing them, however other research has found that reading and writing text messages almost equally impaired driving performance [1,12].…”
Section: Introductionmentioning
confidence: 99%